In-situ monitoring of polymer mechanochemistry: what can be learned from small molecule systems - Willis-Fox, Niamh (Frontiers in Chemistry, 2024)
Using mechanical energy to drive chemical transformations is an exciting prospect to improve the sustainability of chemical reactions and to produce products not achievable by more traditional methods. In-situ monitoring of reaction pathways and chemical transformations is vital to deliver the reproducible results required for scale up to realize the potential of mechanochemistry beyond the chemistry lab. This mini review will discuss the recent advances in in-situ monitoring of ball milling and polymer mechanochemistry, highlighting the potential for shared knowledge for scale up.